PENGARUH PERPUTARAN MODAL KERJA, STRUKTUR MODAL, DAN UKURAN PERUSAHAAN TERHADAP PROFITABILITAS PERUSAHAAN FOOD AND BEVERAGE - Stevany Febreany, SE., M.Ak. (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2021)
Food and beverage companies are included in companies that are in great demand and needed by the community, which allows it to provide benefits for the company either at this time or in the following years. The high level of consumption and purchasing power of the people is very supportive of the growth of an industry, so that it can significantly increase an investment in an industry and can create stability in the performance of food and beverage companies. This study attempts to analyze the to determine the effect partial rotation and simultaneous working capital, capital structure, firm size on profitability. This research was conducted at the food and beverage sector companies listed on the Indonesian Stock Exchange (BEI) in the period 2014- 2018. The results showed that of testing the simultaneous rotation of working capital, capital structure, and the size of the company have a significant effect on profitability in food and beverage company in 2014-2018.